Development of Hydroponic Plants in Semampir Village, Sidoarjo for Strengthening the Village Community Economy in the New Normal Era - Sholeh, Moch.; Niam, M. Faridun (Bisma : Bimbingan Swadaya Masyarakat, 2024)
The purpose ofthis community is to assist the residents of Semampir Village in making hydroponic plants. Through the Community Development approach, the result of this assistance is that assisted communities have the ability to make hydroponic plants as a planting medium in the yard / yard. The results of this assistance are also able to provide an alternative to strengthening the economy of Semampir residents by meeting the needs of vegetables independently in the situation of social restrictions in the new normal, thus providing economic strengthening for the residents of Semampir Sidoarjo during the pandemic.